The development of an online knowledge-based expert system for machinability data selection - Wong, S.V.; Hamouda, A.M.S. (Elsevier BV, 2003)
The development and implementation of an online knowledge-based system for machinability data selection is presented. Fuzzy logic has been incorporated as the reasoning mechanism behind the system. The system has been developed using object oriented programming, dynamic link library and Active-X control. It has been incorporated and tested into Internet and Intranet environment. Possible implementations of the system are suggested to work on real-world environment. A simplified fuzzy set-handling object has been developed in order to save resources. Weighted-centroid rather than union centroid has been used in output defuzzification. Comparison between these two methods is made and discussed.